A pragmatic randomised controlled trial comparing the efficacy of a femoral nerve block and periarticular infiltration for early pain relief following total knee arthroplasty. (July 2017) - Wall, P. D. H.; Parsons, N. R.; Parsons, H.; Achten, J.; Balasubramanian, S.; Thompson, P.; Costa, M. L.
Abstract : Aims: The aim of this study was to compare the effectiveness of a femoral nerve block and a periarticular infiltration in the management of early post-operative pain after total knee arthroplasty (TKA). Patients and Methods: A pragmatic, single centre, two arm parallel group, patient blinded, randomised controlled trial was undertaken. All patients due for TKA were eligible. Exclusion criteria included contraindications to the medications involved in the study and patients with a neurological abnormality of the lower limb. Patients received either a femoral nerve block with 75 mg of 0.25% levobupivacaine hydrochloride around the nerve, or periarticular infiltration with 150 mg of 0.25% levobupivacaine hydrochloride, 10 mg morphine sulphate, 30 mg ketorolac trometamol and 0.25 mg of adrenaline all diluted with 0.9% saline to make a volume of 150 ml. Results: A total of 264 patients were recruited and data from 230 (88%) were available for the primary analysis. Intention-to-treat analysis of the primary outcome measure of a visual analogue score for pain on the first post-operative day, prior to physiotherapy, was similar in both groups. The mean difference was -0.7 (95% confidence interval (CI) -5.9 to 4.5; p = 0.834). The periarticular group used less morphine in the first post-operative day compared with the femoral nerve block group (74%, 95% CI 55 to 99). The femoral nerve block group reported 39 adverse events, of which 27 were serious, in 31 patients and the periarticular group reported 51 adverse events, of which 38 were serious, in 42 patients up to six weeks post-operatively. None of the adverse events were directly attributed to either of the interventions under investigation. Conclusion: Periarticular infiltration is a viable and safe alternative to femoral nerve block for the early post-operative relief of pain following TKA. Cite this article: Bone Joint J 2017;99-B:904–11.